Quality time : productivity through time management - Van Fleet, David D. (Emerald Publishing Limited : Information Age Publishing, Inc., 2020)
"Managers who focus on time usually concentrate on the wrong things. Quality Time presents a new approach to achieving productivity through time management. Time itself is not what matters but rather how that time is used to achieve individual and organizational goals. Managers who get upset over employees coming to work late or socializing on the job often care more about them "putting in time" than putting their time to good use. Quality Time is for managers and others who care about everyone putting their time to good use to contribute to the value of the organization. Based on unique concepts, Quality Time offers both general and specific information and advice from an individual and a team or group point of view. It is designed so that the manager is involved first and then group or team members are engaged. Through reciprocal communication, all parties can arrive at better uses of time. While focused on managers, anyone can achieve productivity from the use of the unique framework and assessments. Quality Time is readable. It uses straightforward language to involve the reader. It makes learning easier and enjoyable by making the material realistic and interesting. The material is up to date and accurate. But most importantly, Quality Time is different from other time-management books. Most are focused solely on the individual. Quality Time is intended to serve individuals but also the workgroups or teams"-- Provided by publisher.
Keywords: Time management.; Labor productivity.; Supervision of employees.; Business & Economics -- Time Management.; elektronické knihy; electronic books